التوجهات المصرفية في ظل التحديات المالية والنقدية المعاصرة حالة الجزائر - احمد, سبع; سليم, صالحي; رضوان, بكاري (University of eloued جامعة الوادي, 2020)
"شهدت البيئة المالية والمصرفية العالمية عدة تغيرات وتطورات لم تشهدها من قبل, وكان في صدارتها العولمة المالية, والتي أثرت على الجهاز المصرفي , باعتباره احد الركائز الأساسية والممول الرئيسي لعجلة الاقتصاد لكونه تربط بين مجمل نشاطات وقطاعات الاقتصادية, ونظرا للتطورات والتغيرات العالمية السريعة والمتلاحقة التي عرفها القطاع المصرفي في ظل العولمة الملية والتي انعكست بالأثر الايجابي والسلبي على القطاع المصرفية. يواجه الجهاز المصرفي الجزائري العديد من التحديات والمتغيرات العالمية التي تفرض نفسها على السوق العالمي والمحلى, وفي مقدمتها المقررات الجديدة للجنة بازل والتي يجب أن تكون ملزمة لكافة البنوك العالمية إذا ما أرادت الحفاظ تواجدها العالمي, وكذا تحرير تجارة الخدمات المالية والمصرفية, بالإضافة إلى التطورات التكنولوجية والتوسع في المعاملات المالية والمصرفية الالكترونية, وما نتج عنها من زيادة المخاطر المصرفية وتزايد حدوث الأزمات المالية, بحيث أصبح الانشغال الرئيسي للقائمين على الأنظمة المصرفية مواجهة تلك التحديات والتقليل من تداعياتها وأثارها السلبية وتعظيم مكاسبها والمزايا التي تتيحها, والاتجاه نحو الشمولية المصرفية . إن تحديث وعصرنة المنظومة المصرفية الجزائرية أصبح ضرورة ملحة في المرحلة الراهنة لاستكمال مسار الإصلاحات المصرفية في الجزائرية مرتبطا بتطوير الخدمات المصرفية, ودعم القدرة التنافسية للبنوك ومواكبة التطورات العالمية والتغيرات التي عرفها الجهاز المصرفي والعمل على إصلاحه بتبني سبل مواكبة التطورات الراهنة, ومنها الحوكمة المصرفية والصيرفة الإسلامية والشاملة ""The global financial and banking environment has witnessed several changes and developments, that have not been witnessed before, and at the forefront of which was financial globalization, which affected the banking system. As it is one of the main pillars and main financiers of the economy wheel because it links all activities and economic sectors. Also, in view of the rapid and successive global developments and changes that the sector has known. Banking in light of financial globalization, which was reflected in the positive and negative impact on the banking sector. The Algerian banking system faces many challenges and global changes that impose itself on the global and local market. Nevertheless, foremost of which are the new decisions of the Basel Committee, which must be binding on all international banks if they want to maintain their global presence, as well as liberalizing the trade of financial and banking services. In addition to technological developments and expansion. With regard to financial, electronic banking transactions, the resulting increase in banking risks and the increase in the occurrence of financial crises. So, that the main concern of those in charge of banking systems has become facing these challenges, reducing their repercussions, negative effects, maximizing their gains, the advantages that they provide, and the trend towards banking inclusion. Modernizing and modernizing the Algerian banking system has become an urgent necessity at the current stage to complete the path of banking reforms in Algeria linked to the development of banking services, support the competitiveness of banks, keep abreast of global developments ,changes in the banking system and work to reform it by adopting ways to keep pace with current developments, including banking governance and Islamic banking And all-round. "
مذكرة ماستر اقتصاد نقدي وبنكي
Keywords: العولمة المالية، الصيرفي الشاملة، اندماج المصرفي، الصيرفة الإلكترونية، الأزمات المالية، الحوكمة المصرفية، الصيرفة الإسلامية، لجنة بازل، الجهاز المصرفي الجزائري.; financial globalization, comprehensive banking, banking merger, electronic banking, financial crises, banking governance, Islamic banking, the Basel Committee, the Algerian banking system